Efficacy Of Added Effect Of Dry Needling Versus Dry Cupping On Calf Muscles With Conventional Therapy In The Treatment Of Plantar Fascitis - Basu, Soumik; Mulchandani, Kiran; Palekar, Tushar J; Tandon , Vanshika; S Kuber, Rajesh (Journal of Neonatal Surgery, 2025)
Background: Plantar fasciitis (PF) is a common cause of heel pain resulting from inflammation and degeneration of the plantar fascia. While conventional treatments include stretching and orthotics, adjunct therapies like dry needling (DN) and dry cupping (DC) have shown potential benefits. Purpose: This study compared the effects of DN and DC on calf muscles, alongside conventional therapy, in managing PF. Methodology: Thirty participants with unilateral chronic PF were randomly divided into two groups: Group A (DN + conventional therapy) and Group B (DC + conventional therapy). Both groups received six sessions over two weeks. Outcome measures included plantar fascia thickness (via ultrasonography), pain threshold (pressure algometer), and functional mobility (Foot and Ankle Disability Index). Results: Both groups showed significant improvements, with DN yielding greater pain relief and functional gains. Conclusion: DN and DC are effective adjuncts for PF management, with DN offering superior functional outcomes